2012
DOI: 10.1088/0004-637x/752/2/93
|View full text |Cite
|
Sign up to set email alerts
|

EVIDENCE FOR LOW EXTINCTION IN ACTIVELY STAR-FORMING GALAXIES ATz> 6.5

Abstract: We present a search for the [C II] 158µm fine structure line (a main cooling line of the interstellar medium) and the underlying far-infrared (FIR) continuum in three high-redshift (6.6 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 58 publications
9
72
1
Order By: Relevance
“…The first results from these facilities indicated that there was no detectable dust-enshrouded star formation in normal or even extremely bright UV-selected z>5 galaxies (Walter et al 2012;Ouchi et al 2013;González-López et al 2014;Ota et al 2014;Riechers et al 2014;Maiolino et al 2015). Later, some bright z∼5-6 galaxies were weakly detected in the far-IR continuum (Capak et al 2015;Willott et al 2015), but at lower levels than seen in similar galaxies at lower redshifts using well known lower-redshift z∼0-2 IRX-β relations.…”
Section: Introductionmentioning
confidence: 90%
“…The first results from these facilities indicated that there was no detectable dust-enshrouded star formation in normal or even extremely bright UV-selected z>5 galaxies (Walter et al 2012;Ouchi et al 2013;González-López et al 2014;Ota et al 2014;Riechers et al 2014;Maiolino et al 2015). Later, some bright z∼5-6 galaxies were weakly detected in the far-IR continuum (Capak et al 2015;Willott et al 2015), but at lower levels than seen in similar galaxies at lower redshifts using well known lower-redshift z∼0-2 IRX-β relations.…”
Section: Introductionmentioning
confidence: 90%
“…However, these dusty examples may not be representative of typical high-redshift galaxies. There is recent evidence of actively star-forming galaxies at z > 6.5 with little dust obscuration (Walter et al 2012;Kanekar et al 2013;Ouchi et al 2013), and observations suggest that dust extinction is generally decreased in low luminosity and high redshift systems (Bouwens et al 2012). Our current understanding of dust formation at high redshift is therefore still quite incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…A great difference between young (E-galaxy is the youngest) and old galaxies (Arp220 is the oldest) is appreciated, and from the energy distribution it is clear that early universe formations have a dominant THz band content. Indeed, important research is carried out nowadays to clear up the hidden information inside the old universe using THz frequencies [26], [27]. Fig.…”
Section: Remote Space Studymentioning
confidence: 99%
“…Fig. 2.4(c), from [27], compares the SED of several old galaxies, including many spiral and dwarf type galaxies. THz-band spectral information results decisive to observe star-forming environments in those galaxies.…”
Section: Remote Space Studymentioning
confidence: 99%
See 1 more Smart Citation